Investigation of the Impact of Combustion Chamber Geometry on Engine Combustion and Emission Performance Under Various Fuel Injection Timings With Biodiesel Blending - Dongge Wang; Guangyuan Bao; Chao He; Jiaqiang Li; Yanlin Chen; Longqing Zhao; Haisheng Yu (Energy Science & Engineering)
ABSTRACT This study uses AVL FIRE 2020 R1 software for simulation and experimental verification to deeply analyze the impact of combustion chamber geometry and biodiesel on diesel engine performance at different injection timings. The study found that: With the advancement of injection timing, the indicated fuel consumption rate, cylinder pressure and NOx emissions of the two combustion systems increased, while the indicated thermal efficiency, temperature and Soot emissions decreased accordingly; The blending of low calorific value biodiesel will increase the indicated fuel consumption rate of the two combustion systems, but at the same time it can effectively reduce NOx and Soot emissions; The T: Turbocharger, C: Charger air cooling, D: Diesel particle filter (TCD) combustion system improves the utilization rate of cylinder air due to its unique combustion chamber geometry, thereby improving combustion performance. Compared with the Omega combustion system, the indicated thermal efficiency of the TCD combustion system increased by 6.16% to 8.38% and the indicated fuel consumption rate decreased by 5.80% to 7.73% when burning four types of fuel. In addition, the in‐cylinder pressure and temperature increased, and it performed better in reducing Soot emissions. The research results show that the TCD combustion system can effectively improve the combustion and emission performance of diesel engines, provide data support for the development of diesel engine combustion systems and the combustion of oxygen‐containing fuels in plateau environments, and provide an important reference for energy conservation and emission reduction.